Production of Σ(1385)± and Ξ(1530)0 in proton–proton collisions at √s = 7 TeV - Alice Collaboration; Abelev, B.; Adam, J.; Adamovã, D.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agostinelli, A.; Agrawal, N.; Ahammed, Z.; Ahmad, N.; Ahmed, I.; et al. (Springer New York LLC, 2015)
The production of the strange and double-strange baryon resonances ((1385)±, (1530)0) has been measured at mid-rapidity (|y|< 0.5) in proton–proton collisions at √s = 7 TeV with the ALICE detector at the LHC. Transverse momentum spectra for inelastic collisions are compared to QCD-inspired models, which in general underpredict the data. A search for the φ(1860) pentaquark, decaying in the π channel, has been carried out but no evidence is seen.
Keywords: Physics; Rapidity; Pentaquark; Particle physics; Baryon; Production (economics); Large Hadron Collider; Proton; Nuclear physics; Quantum chromodynamics; https://purl.org/pe-repo/ocde/ford#1.03.04